Habermann and Pommer (1991) Revisited: Decoding the Mechanism of a Sulfide Storing Microbial Fuel Cell Anode - Erik Lindemann; Inês Didier; Uwe Schröder (ChemElectroChem)
In 1991, Habermann and Pommer published their work on a microbial fuel cell based on sulfide (S2−) mediation at cobalt hydroxide modified graphite anodes. Despite the promising character of the presented concept, literature does not show any follow‐up study or successful reproduction of the results. The common denominator among all further studies that involve sulfide oxidation is the working electrode: The use of plain graphite instead of cobalt impregnated graphite results in irreversible electrode blockage by build‐up of elemental sulfur (S0). In this—purely abiotic—study, the electrochemical properties of cobalt‐deposited electrodes are investigated when brought in contact with sulfide‐containing solutions. This study thereby shows that cobalt acts as a catalyst accelerating the oxidation of S2− to higher oxidation products, thereby avoiding sulfur build‐up on the electrode surface. The sulfide oxidation can proceed directly at the cobalt oxide surface, or via a soaking and subsequent oxidation mechanism. In this process, the cobalt layer itself is “charged” by transformation to cobalt sulfide (CoS), which is subsequently “discharged” oxidatively resulting in the production of current. The insights presented here pave the way for a replication and utilization of the original results by Habermann and Pommer.